Do território à territorialidade: construção do espaço do Assentamento do MST Lagoa do Junco em Tapes, RS - Naiara Machado da Silva; Aline Reis Calvo Hernandez (Confins)
This article discusses and analyzes aspects related to the territory and territoriality constituted by the families of farmers from Lagoa do Junco settlement, which for 23 years have been established in the city of Tapes, in the state of Rio Grande do Sul, Brazil. The data presented in the study of case integrate a broader research developed in the dissertation of Professional Masters in Environment and Sustainability of UERGS, whose scope was the elaboration and the confrontation of the social representations on the Landless, the MST and the Settlement, from three data streams. In these, from the contents seized in the interviews with settlers, the themes on territory and territoriality emerge as relevant category of analysis. In the process of territorialization, the settlers, who are part of the Movement of Landless Rural Workers (MST), have begun to re-signify the occupied space. This territory, as well as a collective conquest of land and labor, was incorporated as an identity for the settlers, integrating the identity of the Landless people, which they have preserved for decades. Accordingly, a territoriality that emphasizes subjective and symbolic aspects is evidenced. Cooperation is revealed as a fundamental dimension which establishes itself as a combat force, identity and work, on the part of the settlers. It also stands out a sense of accomplishment expressed by the settlers when referring to the work developed. Through production, the vision of the people of the city was transformed from the presentation, marketing and consumption of food. A collective work that has been evolving towards a production that privileges sustainability, the environment and people.